Electronic business of Ukrainian trade enterprises under martial law and methods of its stimulation - SHCHURENKO, Sergii (Ways to Improve Construction Efficiency, 2025)
The article is devoted to studying the peculiarities of the functioning of electronic business in Ukrainian trade enterprises and substantiating the methods of its stimulation under martial law. The relevance of the topic is determined by the transformation of e-commerce into a key factor of the country’s economic resilience, which requires scientific understanding of its adaptive potential in crisis conditions. The author analyzes the dynamics of key market indicators and systematizes scientific research on this issue, as well as identifies the main directions for adapting business models to modern challenges. It has been established that the e-commerce sector demonstrates significant adaptive potential and resilience despite the destructive impact of external factors. This approach allows for a comprehensive assessment of the industry’s condition and the formation of a theoretical foundation for developing mechanisms of state support. The author emphasizes the importance of combining state policy instruments, business strategies, and technological solutions to ensure the sustainable development of the sector. The role of developing e-government and electronic document management systems, particularly the “Diia.Business” platform, is highlighted in simplifying online entrepreneurship. Special attention is paid to the analysis of the financial and economic architecture of state support, which is considered a catalyst for digital transformation and modernization of payment infrastructure. It is emphasized that a synergistic effect is achieved through the integration of stimulation measures with the development of e-government systems and the strengthening of cybersecurity resilience. The study identifies the existence of systemic barriers and a lack of public investment that hinder the development of the industry, particularly in the logistics, financial, and regulatory spheres. The necessity of applying a comprehensive approach to stimulating electronic business is substantiated, as it will enable the transformation of the crisis period into a phase of accelerated digital modernization. General scientific and practical recommendations are provided to enhance the resilience and competitiveness of the national e-commerce market.